Training the next generation of delivery science researchers: 10‐year experience of a post‐doctoral research fellowship program within an integrated care system - Richard W Grant; Julie A Schmittdiel; Vincent X Liu; Karen R Estacio; Yi‐Fen Irene Chen; Tracy A Lieu (Wiley, 2024)
Abstract Introduction Learning health systems require a workforce of researchers trained in the methods of identifying and overcoming barriers to effective, evidence‐based care. Most existing postdoctoral training programs, such as NIH‐funded postdoctoral T32 awards, support basic and epidemiological science with very limited focus on rigorous delivery science methods for improving care. In this report, we present the 10‐year experience of developing and implementing a Delivery Science postdoctoral fellowship embedded within an integrated health care delivery system. Methods In 2012, the Kaiser Permanente Northern California Division of Research designed and implemented a 2‐year postdoctoral Delivery Science Fellowship research training program to foster research expertise in identifying and addressing barriers to evidence‐based care within health care delivery systems. Results Since 2014, 20 fellows have completed the program. Ten fellows had PhD‐level scientific training, and 10 fellows had clinical doctorates (eg, MD, RN/PhD, PharmD). Fellowship alumni have graduated to faculty research positions at academic institutions (9), and research or clinical organizations (4). Seven alumni now hold positions in Kaiser Permanente's clinical operations or medical group (7). Conclusions This delivery science fellowship program has succeeded in training graduates to address delivery science problems from both research and operational perspectives. In the next 10 years, additional goals of the program will be to expand its reach (eg, by developing joint research training models in collaboration with clinical fellowships) and strengthen mechanisms to support transition from fellowship to the workforce, especially for researchers from underrepresented groups.